(untitled) (Journal of the College of Basic Education, 2022)
The aim of the present study is to evaluate the frequency of oral protozoa (Entamoeba gingivalis and Trichomonas tenax) among patients with dental prosthesis and study the association between sex, age with the presence of thisParasites.40 presented both protozoa of 54 examined patients (26 male and 28female),18 patients were over 50 years and the reminder were aged from 20 to50 years.E. gingivalis was found in 38(70.37 %) patient,35(64.81% )single and3(5.55 %) mixed with T. tenax., T. tenax was found in 5 (16.66 %) patients, 2(3.70/) single and 3mixed.The highest rate of infection was 83.33 % in patient with aged ovar 50years and 46.66 %,76.29 % in patients aged from 20-35 and 35-50 respectively.Significant difference (p<0.05) was recorded between the age groups.